Taxonomy of the Panorpa guttata group (Mecoptera: Panorpidae), with descriptions of fourteen new species from China - Wang, Ji-Shen; Gong, You-Jing (Zootaxa, 2021)
Panorpa Linnaeus, 1758 is the largest genus in the scorpionfly family Panorpidae. It is considered a paraphyletic taxon and needs further revisions. In this paper, we present a taxonomic study of the Panorpa guttata group, including 23 closely related species, with fourteen species new to science: Panorpa caoweii Wang, sp. n., Panorpa dali Wang, sp. n., Panorpa duanyu Wang & Gong, sp. n., Panorpa hani Wang, sp. n., Panorpa hirundo Wang, sp. n., Panorpa huangguiqiangi Wang, sp. n., Panorpa jiangrixini Wang, sp. n., Panorpa jinfoshana Wang, sp. n., Panorpa latiloba Wang, sp. n., Panorpa nanzhao Wang, sp. n., Panorpa stella Wang, sp. n., Panorpa substricta Wang, sp. n., Panorpa xiaofeng Wang & Gong, sp. n., and Panorpa xuzhu Wang & Gong, sp. n. We also provide a distributional map, keys to species, and discussions regarding the taxonomic implications and biological information of the P. guttata group.